Automatic execution of semantic web service - Chen, Jiadong. (2011)
The first part of this dissertation starts from the introduction of the basic concepts and structures of OWL, and then it goes on to the methodology to develop OWL ontology. After OWL, we give a brief introduction of SOAP/WSDL based web service which is comprised of SOAP, WSDL and UDDI. However, WSDL descriptions by themselves do not provide sufficient information to ascertain the correct usage of the service. After illustrating the benefits of the richer service descriptions supported by OWL-S, it’s time to get into OWL-S which is an OWL-based Web Service Ontology, we illustrate the three concepts of OWL-S which consists of service profile, process model and service grounding. Then we continue to describe the OWL-S development paradigm and give a quick view on the semantic web service execution environments. Finally we conclude with a brief look at the OWL-S tools and extensions. The second part is about automatic execution of OWL-S semantic web service which first describes the problems in automatic executions of OWL-S semantic web service caused by the mismatches between OWL-S input/output classes and WSDL request/response messages. Then we use the approach of OWL-S/WSDL grounding to provide the mapping mechanism to solve the incompatibility between XML schema types and OWL classes when OWL-S descriptions use OWL classes as the input/output in the service model to invoke the web service in WSDL. In the design of automatic execution of OWL-S service, we come up with an OWL-S framework based on the generic OWL-S/WDSL grounding process to enable automatic OWL-S service execution and detailed runtime interactions occur in executing the OWL-S atomic process step by step. We also highlight the design issues and conclude with the limitations of OWL-S framework. The third part of this dissertation presents a derailed implementation of automatic execution of an OWL-S atomic process using OWL-S/WSDL grounding step by step, focusing primarily on the XSLT transformation of the OWL-S input class to the WSDL request messages at OWL-S request, and the WSDL response message to the OWL-S output class at OWL-S response.